Cement augmentation as revision strategy for loosened thick-diameter non-fenestrated iliac screws – A biomechanical analysis. (May 2019) - Decker, Sebastian; Meyer, Moritz; Müller, Christian W.; Krettek, Christian; Ferle, Manuel
Abstract: Background: Loosened/pulled-out iliac screws can be a challenging complication, as revision opportunities are limited because more distal anchorage is impossible. Insertion of thick-diameter screws is an option in cases with loosened thin-diameter screws. However, this is occasionally infeasible in patients with loosened thick-diameter screws. Therefore, this study aimed to biomechanically analyze whether loosened/pulled-out thick iliac screws regain strong anchorage following cement augmentation. Methods: Six human pelvis specimens were dissected to isolate 12 hemipelves, and 9 × 80 mm iliac screws were implanted. The pullout maneuver was performed followed by cement augmentation of the same screw within the same screw hole. After cement hardening, pullout was performed again. Forces needed for pullout and the insertion torque were measured for the 12 iliac screws. Findings: Cement augmentation significantly increased stability, with the pullout forces required being as high as 953.23 N (standard deviation [SD] 1070.46 N; median 306.30 N) for the uncemented screws and 2897.53 N (SD 585.83 N; median 2907.81 N) after cement augmentation (p < 0.001). No correlation was found between insertion torques and pullout forces. Interpretation: While revision of loosened iliac screws can often be achieved using higher diameters, this method is limited by the thickness of the screws already in place. We demonstrated that cement augmentation significantly increases stability even in thick-diameter screws, achieving more pullout stability than before the initial pullout. This method may be a cost-effective and rapid option for revision, even with significant defects and with no thicker-diameter iliac screw being available. Highlights: Loosened/pulled-out iliac screws can be a challenging complication. Thick-diameter screws may be used to replace loosened thin-diameter screws. However, this is occasionally infeasible with loosened thick-diameter screws. Cement augmentation significantly increases stability with thick-diameter screws. Cement augmentation seems a cost-effective and rapid option for revision surgery.